Bajo las luces de Tana . Under the Lights of Tana - Soler, Joan (Cinefilms Production, 2007)
Verzio FF Submission Madagascar is one of the poorest countries in the world and the most vulnerable members of its society are women. Without economic resources of any kind, they survive on the streets, thanks to money they or their children earn as beggars. In some cases, these women resort to prostitution. This film depicts life in a poor country where informal activities and informal living is far more popular than the regular and formal way of subsisting, where poverty tears apart families and where running away from the responsibilities of being a father or a husband seems to be the best solution for the men.